Deviation of dental implants placed using a novel 3d-printed surgical guide: An in vitro study - Etajuri, Enas Abdalla; Sulaiman, Eshamsul; Mahmood, Wan Adida Azina; Ibrahim, Norliza; Buzayan, Muaiyed Mahmoud; Raja Mohd, Noorhayati (Wroclaw Medical University, 2020)
Background. There is very little literature available on the reliability of the rapid prototyping technology in the production of three-dimension (3D)-printed surgical guides for accurate implant placement. Objectives. The aim of the study was to evaluate the deviation of implant placement performed with a surgical guide fabricated by means of the rapid prototyping technique (the PolyJet™ technology). Material and methods. Twenty sheep mandibles were used in the study. Pre-surgical cone-beam computed tomography (CBCT) scans were acquired for the mandibles by using the Kodak 9000 3D cone-beam system. Two implants with dimensions of 4 mm in diameter and 10 mm in length were virtually planned on the 3D models of each mandible by using the Mimics software, v. 16.0. Twenty surgical guides were designed and printed using the PolyJet technology. A total of 40 implants were placed using the surgical guides, 1 on each side of the mandible (2 implants per mandible). The post-surgical CBCT scans of the mandibles were performed and superimposed on the pre-surgical CBCT scans. The amount of deviation between the virtually planned placement and the actual implant placement was measured, and a descrip-tive analysis was done. Results. The results showed that the mean deviation at the implant coronal position was 1.82 ±0.74 mm, the mean deviation at the implant apex was 1.54 ±0.88 mm, the mean depth deviation was 0.44 ±0.32 mm, and the mean angular deviation was 3.01 ±1.98°. Conclusions. The deviation of dental implant placement performed with a 3D-printed surgical guide (the PolyJet technology) is within the acceptable 2-millimeter limit reported in the literature. © 2020 by Wroclaw Medical University.